2014
DOI: 10.1167/iovs.13-13492
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Luminance and Accommodation Stimuli on Pupil Size and Pupil Center Location

Abstract: Variations in luminance and accommodation influence pupil size, but only the former affects pupil center location significantly. Pupil center shifts are too small to be of concern in fitting progressive addition lenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
47
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 15 publications
6
47
2
Order By: Relevance
“…Qi et al reported a positive correlation in horizontal and vertical components of kappa angle in preoperative sitting position measured via Pentacam and intraoperative supine position measured via the Allegretto Wavelight Excimer Laser System (WaveLight Laser Technologie AG). [38] Therefore, although our measurement values may be affected by change in posture due to the effect of cyclotortion, and also due to comparing measurements across different platforms, a positive correlation between measured values in different postures and platforms has already been previously described. [39] In retrospect, it may still be beneficial to have postoperative topography to confirm accuracy of centration analysis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Qi et al reported a positive correlation in horizontal and vertical components of kappa angle in preoperative sitting position measured via Pentacam and intraoperative supine position measured via the Allegretto Wavelight Excimer Laser System (WaveLight Laser Technologie AG). [38] Therefore, although our measurement values may be affected by change in posture due to the effect of cyclotortion, and also due to comparing measurements across different platforms, a positive correlation between measured values in different postures and platforms has already been previously described. [39] In retrospect, it may still be beneficial to have postoperative topography to confirm accuracy of centration analysis.…”
Section: Discussionmentioning
confidence: 90%
“…Mathur et al [38] studied the change in position of pupil center in relation to pupil size changes due to luminance adjustments. The average shift of pupil center was 0.12 mm nasally, with maximum shifts of 0.5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is known that accommodation plays a significant role in controlling pupil size,4 the influence of accommodation on pupil size in presbyopes is expected to be relatively small and is irrelevant when comparing the effect of luminance for the conditions of daytime outdoor vision and night time driving.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that pupil size decreases with increasing luminance 14. The strongest patient-related determinative factor for pupil size has been shown to be age 59.…”
mentioning
confidence: 99%
“…The pupillary centroid shifts with pharmacological dilatation, change in accommodation, illumination and during excimer ablation …”
mentioning
confidence: 99%